2017
DOI: 10.1126/scisignal.aai7905
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid-Angptl4-ceramide axis induces insulin resistance through PP2A and PKCζ

Abstract: Chronic glucocorticoid exposure is associated with the development of insulin resistance. We showed that glucocorticoid-induced insulin resistance was attenuated upon ablation of Angptl4, a glucocorticoid target gene encoding the secreted protein angiopoietin-like 4, which mediates glucocorticoid-induced lipolysis in white adipose tissue. Through metabolomic profiling, we revealed that glucocorticoid treatment increased hepatic ceramide concentrations by inducing enzymes in the ceramide synthetic pathway in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
(87 reference statements)
2
31
0
Order By: Relevance
“…Intriguingly, ceramides were found to play a role in insulin resistance induced by saturated fatty acids . It has also been shown that ceramides can impair glucose metabolism by acting on Akt signalling pathways through PP2A and/or PKCζ mediators . Chen et al .…”
Section: Ceramides and Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Intriguingly, ceramides were found to play a role in insulin resistance induced by saturated fatty acids . It has also been shown that ceramides can impair glucose metabolism by acting on Akt signalling pathways through PP2A and/or PKCζ mediators . Chen et al .…”
Section: Ceramides and Insulin Resistancementioning
confidence: 99%
“…Chen et al . showed that ceramides impair glucose metabolism and induce insulin resistance through PP2A‐ and PKCζ‐dependent mechanisms . Mahfouz et al .…”
Section: Ceramides and Insulin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…These two inhibitory mechanisms are independent, targeting distinct protein domains. They appear to have cell type-dependent functional dominance (Bourbon et al 2002, Stratford et al 2004, Fox et al 2007, but operate concurrently in at least some instances (Dey et al 2007, Chen et al 2017. Despite the direct link to insulin action, however, the fact that these mechanisms have been identified primarily in muscle has prompted some researchers to raise doubts as to their relevance in other tissues (Petersen & Shulman 2017).…”
Section: Ceramides and Sphingolipidsmentioning
confidence: 99%